The Effectiveness of Platelet-Rich Plasma as a Carrier of Stem Cells in Tissue Regeneration: A Systematic Review of Pre-Clinical Research - Anitua, Eduardo; Troya, María; Tierno, Roberto; Zalduendo, Mar; Alkhraisat, Mohammad H (Cells, tissues, organs, 2021)
Fibrin, as a physiological scaffold, presents many advantages compared to synthetic materials, such as controllable degradation, non-toxic byproducts, and excellent biocompatibility. The use of stem cells along with the biomimicking scaffolds and signalling factors would complete the triad of the tissue engineering approach. In this context, the aim of this narrative review is to compile the current evidence in vitro and in vivo regarding the combination of platelet-rich plasma (PRP) scaffolds and adult stem cells focusing on the regenerative medicine field according to the clinical application. A total of 1,832 articles were identified during the systematic literature search through three databases (Google Scholar, PubMed, and Web of Science). A total of 18 publications reaching the inclusion criteria were finally included in this review. According to the results, the combination of PRP and stem cells improved osteogenic and cartilage regeneration. However, regarding periodontal regeneration conflicting results were reported. Many other pathologies were also investigated, and even though no general conclusions were able to be obtained, most of them supported the superior performance of PRP-based scaffolds seeded with stem cells. Finally, the lack of a comprehensive description of the PRP composition makes it difficult to compare them and to draw robust conclusions. Therefore, an accurate and complete description of the product needs to be detailed in upcoming scientific publications.